Foam Glass Lightened Sorel's Cement Composites Doped with Coal Fly Ash - Pivák, Adam; Pavlíková, Milena; Záleská, Martina; Lojka, Michal; Lauermannová, Anna-Marie; Faltysová, Ivana; Jankovský, Ondřej; Pavlík, Zbyšek (Materials (Basel, Switzerland), 2021)
Lightweight Sorel's cement composites doped with coal fly ash were produced and tested. Commercially available foam granulate was used as lightening aggregate. For comparison, reference composites made of magnesium oxychloride cement (MOC) and quartz sand were tested as well. The performed experiments included X-ray diffraction, X-ray fluorescence, scanning electron microscopy, light microscopy, and energy dispersive spectroscopy analyses. The macro- and microstructural parameters, mechanical resistance, stiffness, hygric, and thermal parameters of the 28-days matured composites were also researched. The combined use of foam glass and fly ash enabled to get a material of low weight, high porosity, sufficient strength and stiffness, low water imbibition, and greatly improved thermal insulation performance. The developed lightweight composites can be considered as further step in the design and production of alternative and sustainable materials for construction industry.
Keywords: Sorel’s cement; construction composites; coal fly ash; foamed glass; hygrothermal performance; structural parameters